2021
DOI: 10.1097/spv.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

Does a Recent Urinary Tract Infection Increase the Risk of Postprocedure Urinary Tract Infection After Onabotulinum Toxin A?

Abstract: Objectives: To evaluate the risk of post-procedure urinary tract infection after injection of onabotulinumtoxin A in women who had a urinary tract infection within 30 days prior to procedure. Methods:This was a retrospective cohort study of women who underwent their first injection of onabotulinumtoxin A from 2010 to 2016. Two cohorts were identified: 1) recent urinary tract infection (within 30 days prior to injection); and 2) no recent urinary tract infection. Our primary outcome was urinary tract infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A treatment with ciprofloxacin started prior to injection decreased the risk of UTI when compared to a treatment started after injection [ 26 ]. On the other hand, when procedures are performed in patients who had a recent preoperative UTI but received prophylactic perioperative antibiotics during the intervention, no increase in postoperative UTIs could be found in a trial by Brickhaus and colleagues [ 27 ]. Consequently, certain authors recommend the use of perioperative antibiotics [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A treatment with ciprofloxacin started prior to injection decreased the risk of UTI when compared to a treatment started after injection [ 26 ]. On the other hand, when procedures are performed in patients who had a recent preoperative UTI but received prophylactic perioperative antibiotics during the intervention, no increase in postoperative UTIs could be found in a trial by Brickhaus and colleagues [ 27 ]. Consequently, certain authors recommend the use of perioperative antibiotics [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[88][89][90][91][92][93] We think it is safer to perform this procedure in the face of a negative urine culture, although Bickhaus they stated that performing a first injection of onabotulinum toxin A within 30 days of urinary tract infection does not increase the odds of post-procedure urinary tract infection. 94 Huang showed that intradetrusor injection of onabotulinum toxin A at the time of HoLEP is safe and is associated with improved urinary incontinence scores and AUA Symptom Score. 95 We performed toxin injection after the endoscopic disobstructive prostatic operation, because sometimes we observed the patient for persistent LUTS after the operations or to wait till the complete resolution of inflammatory field.…”
Section: Discussionmentioning
confidence: 99%
“…Although UTI can be treated with antibiotics, the occurrence of this adverse event might prohibit patients from receiving this treatment after their first UTI experience following Botox injection. A recent study reported that the administration of a first Botox injection within 30 days of a UTI does not increase the risk of post-Botox UTI [ 141 ]. Patients with prior prolapse surgery or with recurrent UTI may have a higher risk of UTI after a Botox procedure [ 142 ].…”
Section: Potential Clinical Applications Of Botox On Recurrent Uti De...mentioning
confidence: 99%